2019
DOI: 10.3390/jcm8101575
|View full text |Cite
|
Sign up to set email alerts
|

Pain Perception and Acceptance of Illness in Patients Undergoing Phacoemulsification Cataract Surgery under Drip Anesthesia

Abstract: For many years, cataracts have been the main cause of vision loss and vision impairments in the world (43% and 33%, respectively). Currently, the most common surgical method for treating cataracts is phacoemulsification. The aim of this study was to assess the pain perception and acceptance of illness connected with awaiting phacoemulsification cataract surgery under intravenous drip anesthesia, as well as to determine the effect of selected sociodemographic factors on the above. Methods: The study was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
0
9
0
1
Order By: Relevance
“…While some previous studies analyzed subjective experiences of patients before and during cataract surgery, most of them focused on preoperative anxiety, pain, or visual sensations during the operation. 2 , 5 , 6 , 9–25 To the best of our knowledge, none of the previous studies aimed to identify the least positive components of the phacoemulsification procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some previous studies analyzed subjective experiences of patients before and during cataract surgery, most of them focused on preoperative anxiety, pain, or visual sensations during the operation. 2 , 5 , 6 , 9–25 To the best of our knowledge, none of the previous studies aimed to identify the least positive components of the phacoemulsification procedure.…”
Section: Discussionmentioning
confidence: 99%
“… 7 , 8 In addition, there are papers, which describe the subjective feelings of patients during the phacoemulsification procedure, such as the perception of pain, fear, visual and auditory sensation, and duration of the surgery. 9–19 Comparative analysis of the subjective opinions of patients who underwent cataract surgery for one or both eyes demonstrated that the first procedure was associated with higher levels of stress and anxiety, whereas the second one was accompanied by more severe subjective pain. 6 , 20–25 …”
Section: Introductionmentioning
confidence: 99%
“…A low score is considered to be less than 20 points, and values above 30 points indicate a high level of acceptance of one's disease. An average score ranges from 20 to 30 points (Kowalczyk et al, 2019). Therefore, the lower the score, the less the patient tolerates their illness.…”
Section: Assessment Of the Acceptance Of Illness Scalementioning
confidence: 99%
“…Cataracts are defined as the opacity of the crystalline lens and are one of the most prevalent ocular pathologies today, particularly age-related cataracts. They are the leading cause of vision loss [1] and visual impairment around the world (43% and 33%, respectively) [2].…”
Section: Introduction 1phacoemulsificationmentioning
confidence: 99%
“…Cataract surgery is currently a quick, painless, highly effective, and low-risk procedure [3]. About 90% of operated patients are able to see better after the operation [4], which can be undertaken at any stage of cataract development [2].…”
Section: Introduction 1phacoemulsificationmentioning
confidence: 99%